(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Innovations are essential for businesses to thrive in recent dynamic and competitive environment. By continuously seeking out new ideas, technologies, and ways of doing things, businesses can drive growth, improve efficiency, meet evolving customer needs, and create value for stakeholders. Embracing a culture of innovation and investing in research, development, and experimentation are key to unlocking the full potential of innovation in business. The paper presents the essence of innovation strategy, the main priorities for applying innovation strategy, the importance of innovation for companies.